Coverage Vol. 15 No. 1 - ., Editorial (AUSTENIT, 2023)
Austenit is a peer-reviewed journal that is regularly published twice times (April and October) a year by Mechanical Engineering Department of Politeknik Negeri Sriwijaya and managed by an experienced editorial board coming from universities in Indonesia and overseas partners. This journal is a highly quality to bridge the results of applied and vocational research in the form of scientific works which have never been published in the other media. The works are in the field of mechanical engineering which includes product design and engineering, energy conversion, metallurgy engineering and sciences, construction, mechanical maintenance and repair, renewable energy and sustainability, and mechanization-control. There are ten articles in this Vol.15 No.1 edition issue written by researchers and Industry expert practitioners from VietNam and Indonesia. The VietNam researchers from Dong Nai Technology University. The Indonesian researchers from Universitas Sriwijaya, Politeknik Astra, Universitas Tridinanti Palembang, Politeknik Negeri Jakarta and Politeknik Negeri Sriwijaya as well Industry Expert from PT. Pusri Palembang. Each article has been selected by the editorial team and passed the single-blind review stage by highly qualified reviewers.